KAJIAN ELEMEN PEMBENTUK IDENTITAS GENDER PADA RESTORAN BERTEMA PEREMPUAN DI KOTA BANDUNG - AAN SETIAWATI; IMAM SANTOSA; WIDIHARJO WIDIHARJO (Serat Rupa: Journal of Design, 2016)
This research is a study of gender identity element at female-themed restaurants in Bandung city. The case study of this research is restaurant Roemah Nenek and Nanny's Pavillon. This study is a qualitative test based on the theory that concern in the aspects of the implementation of gender identity in the restaurant interior elements. The result form this research is gender identity context at Restoran Roemah Nenek and Nanny's Pavillon is formed from the brand and the nature of the interior elements that have a correlation with the stereotypical understanding about the nature of female. Restaurant interior elements generally show consistency of meaning, that is the concept of the restaurant has a similar meaning and mutual support against the interior elements as identity of the restaurant. Thus, there is no difference in meaning and elements correlation to the perception of the observer about the restaurant. Perception observers show the same consistency of expression between the nature of objects and the nature that appear on female characters.Â Keywords: female; gender; identity; interior; thematicÂ